Tid att städa Om vardagsstädningens praktik och politik - Ambjörnsson, Fanny (Kriterium, 2018)
"Cleaning is central to all societies. It is an experience shared by almost everyone. A clean home is related to both respectability and status. The mere execution of the deed - whether it concerns taking care of other peoples' dirt or ones' own - ranks, however, strikingly low, contaminating everyone who has to perform it. Therefore, cleaning is permeated by hierarchies of for instance gender, class, sexuality and race. Even though cleaning activates several existential and politically burning questions, it is surprisingly non-existing in research. The point of departure for this study is anthropological, and the material is a number of interviews with Swedes of today about their habits and experiences of cleaning. In focus are questions of cleaning as a cultural symbol, a bodily practice, temporality, and as an expression of taking care of decay. By investigating the meaning of what cleaning means to people - how it is experienced, organized, and distributed in everyday life - I want to discuss how such a central part of our existence is regarded as something that lacks value."